Benefactive declarative sentences in Indonesian: The role of the beneficiary in social behavior representation - Asrumi , Asrumi; Suyanto, Budi; Dewi Setiari, Agustina; Muji, Muji (Politeknik Negeri Bali, 2023)
Language shows a nation's character. Can Indonesian sentences with the predicate benefactive verbs show the character of the Indonesian nation? Benefactive sentences are sentences that have a subject argument as the beneficiaries and an object argument as the agent or vice versa. Subjects as agents and objects as beneficiaries. Beneficiaries can be oneself and can also be other people or personal things. In the Indonesian language by the beneficial declarative sentences, it can be determined the dominance of the beneficial. The problem is, what is the impact of the dominance of the beneficiary role on the behavior of Indonesian language users and what is the agent's relationship with our social beneficiaries and its social impact? The purpose of this study is to reveal the impact of dominance of the role of beneficiary in the benefactive verb on the declarative sentence of the Indonesian language, and the relationship of the agent with the beneficiary of circumstances or other people and their social impact. This research is qualitative research. The research data is in the form of declarative sentences in Indonesian which are predicated of benefactive verbs in people's speech, elementary-high school Indonesian language books, middle school economics books, and research data exploration. Research data was collected using observation and documentation methods using note-taking techniques and analyzed using distributional methods, interpretation, and analysis of meaning components. The results of this research can be concluded that beneficial declarative sentences in Indonesian show the behavior of the Indonesian people which is selfish, liberalist, and hedonistic, not socialist. The implications of these characteristics are for the nation's behavior, including corrupt public officials (only concerned with personal, family, and group profits)